STRATEGI PENGEMBANGAN PARIWISATA BALI MENGHADAPI PANDEMI COVID-19 MELALUI PERAN ASOSIASI PROFESI PARIWISATA - Sugita, I Wayan; Wisnawa, I Made Bayu (Jurnal Manajemen Pelayanan Hotel, 2021)
The COVID-19 pandemic has caused a decline in tourism in Bali. Tourist visits decreased drastically, causing a significant decrease in income for companies engaged in the tourism sector. This has a broad impact on the economy of Bali, considering that tourism is the main motor of the Balinese economy. The government as a decision maker and policy maker is experiencing difficult times, because the health protocol demands restrictions on the movement of the masses, while the economy cannot run without community activities. One of Bali's tourism stakeholders is the Bali tourism professional association which has an important role in helping the government overcome the crisis caused by the COVID-19 pandemic. This study aims to (i) identify the role of tourism professional associations and (ii) analyze Bali's tourism development strategies in dealing with the COVID-19 pandemic through the role of tourism professional associations. This research was conducted with a qualitative descriptive approach to obtain an in-depth understanding of the field situation through interviews with tourism expert respondents and practitioners. The results of interviews and ISM questionnaires are used as data sources processed by the ISM (Interpretive Structural Modeling) method. This research is based on the Pentahelix concept which is stated in the Regulation of the Minister of Tourism (Permen) of the Republic of Indonesia Number 14 of 2016 concerning Guidelines for Sustainable Tourism Destinations. The results show that: (i) the role of the tourism professional association is very important in supporting the development of Bali tourism in the face of the COVID19 pandemic, (ii) Bali tourism development strategies, namely: verification of the application of new habits during the COVID-19 pandemic, improving the system and synchronization between government agencies / agencies in managing tourism in accordance with health protocols and continuing to socialize new era customs regulations for hotel and restaurant tourism actors in a sustainable manner. Keywords: Tourism, Covid-19, Pentahelix, Interpretive Structural Modeling, Tourism Professional Association, Health Protocols